Analisis Dan Mitigasi Risiko Keselamatan Transportasi Laut (Boat Penumpang) Menggunakan Metode House of Risk (HOR) dan Diagram Bowtie (Studi Kasus: Rute X) - Anisa Anisa; Defi Irwansyah; Anwar Anwar (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Sea transportation on route X plays a vital role in community mobility but still faces various safety risks that are not yet systematically managed. This study aims to identify risk events and risk agents, determine risk priorities, and propose mitigation strategies for passenger boats. A mixed-method approach was applied, with data collected through field observations and interviews with boat operators, then analyzed quantitatively using the House of Risk (HOR) phases 1 and 2 and the Bowtie diagram. The results identified 10 risk events and 18 risk agents, with the highest risk being boat overload and the lowest risk propeller entanglement in fishing nets. Pareto analysis revealed 9 dominant risk agents and 14 proposed mitigation actions. The Bowtie diagram illustrated the relationship between causes, events, and impacts with 6 main top events. Therefore, operators are recommended to implement and continuously evaluate mitigation strategies to minimize safety risks.